Assessing the predictive capability of N, P, and B diagnosis in cotton crop - Traspadini, Edilaine Istéfani Franklin [UNESP]; Wadt, Paulo Guilherme Salvador; de Prado, Renato Mello [UNESP]; Furtado Oliveira, Douglas; Campos, Cid Naudi Silva (Springer Nature, 2024)
The compositional nutrient diagnosis—CND method is a standard tool for evaluating plant nutritional status. Adjustments are crucial to elevate accuracy. The effectiveness of such methodological refinements should be rigorously assessed through accuracy tests that are benchmarked against the prescient diagnostic analysis—PDA methodology. The objective of this investigation was to refine the CND technique for a more precise evaluation of N, P, and B nutrient status in cotton. The study’s database encompasses 144 data points pertaining to crop yield and foliar nutrient concentrations from cotton plantations in the Cerrado biome of Brazil. Subsequently, the CND norms were established through rigorous calibration. Three separate nutrient-dose trials, each featuring four levels of N, P and B, were carried out to assess plant true nutritional status. Adjustments were made to the nutrient responsiveness range—NRr (0.5 and 1.0), while yield response—YR were scrutinized at threshold levels (5% and 10%). The prerequisites for achieving high diagnostic accuracy were nutrient specific. For N, maximal accuracy was linked only to the YR parameter (YR = 10%). For P, the most precise outcomes were attained with a NRr = 0.5 and YI = 5%. For B, highest diagnostic accuracy when the NRr = 1.0 and YI = 10%. These insights highlight the need to fine-tune the CND method for reliable nutritional evaluations and cotton crop productivity optimization.
Keywords: Accuracy; CND method; Diagnostic analysis; Foliar diagnosis; Gossypium hirsutum; Net yield productivity